Management of HCV-Related Liver Disease in Hemophilia and Thalassemia - Rumi, Maria Grazia; Di Marco, Vito; Colombo, Massimo (Seminars in Liver Disease, 2018)
Chronic infection with the hepatitis C virus (HCV) has long been the dominant complication of substitution therapy in patients with inherited blood disorders and the cause of anticipated death due to end-stage liver disease. In hemophilia, transmission of HCV with clotting factors concentrates started to be curbed in the mid-1980s following the adoption of procedures of virus inactivation of concentrates based on heat, whereas in the 1990s treatment of HCV infection with interferon monotherapy was attempted, however, with little success. The advent of combination therapy of interferon with ribavirin led to a substantial improvement of treatment outcome (40% rate of cure), that however was still of limited efficacy in patients with advanced liver disease, those with high load of HCV genotype 1, and patients coinfected with the human immunodeficiency virus. In this latter population, while the course of hepatitis C was accelerated as a consequence of immunodeficiency, the advent of highly active antiretroviral therapy led acquired immunodeficiency syndrome (AIDS) to decline and hepatitis C to progressively emerge as a dominant cause of mortality, in parallel. In patients with thalassemia, transfusion-related transmission of HCV was efficiently interrupted in 1992 with the advent of sensitive screening tests for testing donors for HCV, whereas treatment with interferon and ribavirin of infected thalassemics was constrained by an increased risk of anemia due to the hemolytic properties of ribavirin coupled with interferon-induced bone marrow suppression. The advent of safe and potent regimens based on the oral administration of direct antiviral agents has revolutionized therapy of HCV in patients with congenital blood diseases, providing substantial clinical benefits and making elimination of infection in these populations, possible.
Keywords: hepatitis C; hemophilia; sickle cell anemia; thalassemia; direct antiviral agents